Design Build an Automatic Granulated Sugar Vending Tool Microcontroller Based - A'shar, Yusriza Eka; Hariyadi, Aad; Anshori, Mohammad Abdullah (Politeknik Negeri Malang, 2024)
Trader and distributor of 50 kg of cane sugar from Kebonagung in the District Batu Kota Batu will be packed again, then it will be re-sell to trader small or consumer direct in accordance with request order. Every order of sugar will be made per pack, namely 1 kg, 2 kg and 3 kg and the amount are according to request and there are also those who place orders online via WhatsApp. Sugar distributors are currently still using manual scales to pack the sugar and must measure the sugar to produce a scale according to the weight of the sugar. This study designed an automatic tool to overcome this problem by designing a Microcontroller-Based Automatic Sugar Vending Tool with a sugar capacity of 10kg and a load cell of 5 kg and a sugar ordering application . The resulting tools and applications are can produce tools selling granulated sugar automatically based on purchase weight, a minimum purchase of 500 grams while a maximum of 3 kg, based on a nominal amount of money (rupiah) a minimum purchase of IDR 7,000 while a maximum of IDR 42,000 and after weighing the sugar can be packaged directly using a sealer and the application can be used to place sugar orders between sellers and customers with orders of 1, 2, 3 kg, the quantity ordered, find out sugar orders and delivery costs. The success rate of measurement on the load cell is 10 times with a weight the percentage of success is 99.00%.